Clinical features and prognosis of patients with anti-GBM disease combined with mesangial IgA deposition - Ning, Wei; Zhao, Ya-fei; Liu, Ya-ru; Qi, Yuan-yuan; Zhao, Zhan-zheng (Frontiers in Immunology, 2024)
Introduction Anti-GBM diseases with IgA deposition in the mesangial region are rarely described.The factors influencing renal prognosis in patients with anti-GBM disease combined with mesangial IgA deposition are unknown. Methods We searched the pathological reports of the First Affiliated Hospital of Zhengzhou University from 2015 to 2023 and found that a total of 72 patients with the anti-GBM disease and 25 patients combined with mesangial IgA deposition. We studied the clinical and pathological features, renal prognosis, and the factors affecting renal prognosis in patients with anti-GBM disease combined with mesangial IgA deposition. Results Their median age was 44 years, and their age distribution was unimodal. The proportion of oliguria or anuria in patients with anti-GBM disease combined with mesangial IgA deposition was significantly lower than that in patients with classic anti-GBM disease (13.04 vs. 42.31%, p=0.030). Their 24-hour urinary protein excretion was significantly higher [median:3.25 vs. 1.12g/24h, Interquartile range(IQR):1.032 3.945 vs. 0.63 1.79g/24h, p=0.020], serum creatinine (SCr) level at the initial diagnosis was lower(median:456.0 vs. 825.5μmol/L, IQR:270.0 702.0 vs. 515.8 1231.2μmol/L, p=0.002), peak SCr level was lower (median: 601.0 vs. 907.2μmol/L, IQR: 376.5 937.0 vs. 607.0 1361.2μmol/L, p=0.007), and their serum complement 3(C3) level was higher(median: 1.275 vs. 1.015g/L, IQR:1.097 1.462 vs. 0.850 1.220g/L, p=0.027). They had better renal outcomes during follow-up (p<0.001). After adjustment for hypertension, oliguria or anuria, and crescents%, IgA deposition in the mesangial region was still an independent protective factor (p=0.003) for ESRD in anti-GBM patients. Hypertension (p=0.026) and SCr levels at initial diagnosis (p=0.004) were risk factors for renal prognosis in patients with anti-GBM disease combined with mesangial IgA deposition. Discussion Patients with anti-GBM disease combined with mesangial IgA deposition have less severe renal impairment and better renal prognosis than patients with classic anti-GBM disease.